KONFLIK BATIN TOKOH UTAMA NADIRA PADA NOVEL THE HIDDEN KARYA KAK NANA - Mastuti Mastuti; Elsa Mulya Karlina (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the inner conflict experienced by the main character Nadira in the novel The Hidden by Kak Nana using Sigmund Freud's psychoanalytic approach. Inner conflict is an internal conflict between instinctive urges (id), moral demands (superego), and the pressure of reality (ego) experienced by an individual. In this novel, the character Nadira is depicted facing various emotional pressures, ranging from conflicts with her father, social pressure in the Islamic boarding school environment, to losing her husband while pregnant. This study uses a qualitative approach with a literature study method, where primary data is obtained from excerpts from the novel text and secondary data from Freud's psychoanalytic theory. The results of the study show that the forms of inner conflict experienced by Nadira include guilt, anxiety, fear, and loss of identity. This conflict has an impact on behavioral changes, such as becoming quiet, solitary, and emotional. The imbalance between the id, ego, and superego causes the character to use self-defense mechanisms such as repression and rationalization. This study concludes that Freud's psychoanalytic approach can be used effectively to examine the psychological dynamics of characters in literary works, as well as provide an in-depth understanding of the human mental condition that is depicted fictionally.